EUS correlates of disconnected pancreatic duct syndrome in walled-off necrosis - Bang, Ji Young; Navaneethan, Udayakumar; Hasan, Muhammad K.; Hawes, Robert H.; Varadarajulu, Shyam (Endoscopy International Open, 2016)
Background and study aims: Although the diagnostic features of disconnected pancreatic duct syndrome (DPDS) by computed tomography (CT) and magnetic/endoscopic retrograde cholangiopancreatography (MRCP/ERCP) have been established, no such characterization exists for endoscopic ultrasound (EUS). This study describes the imaging features of EUS that accurately define DPDS.Patients and methods: This is a prospective study comprising 21 of 42 patients who underwent EUS-guided drainage of walled-off necrosis (WON) over an 18-month period. Findings on EUS were correlated with CT and pancreatography or surgical pathology when available. DPDS by EUS was defined by the presence of a well-defined fluid collection along the course of the main pancreatic duct with the upstream pancreatic parenchyma and duct terminating into the fluid collection. The main outcome measure was to assess the accuracy of EUS in diagnosing DPDS by correlation with CT and pancreatography or surgical pathology.Results: Twenty-one patients with WON (median age 55 years; 15 males) constituted the study cohort. Median duration of pancreatitis was 12 weeks (range 5 – 20) and median WON size was 120 mm (range 40 mm to 200 mm). At EUS, the upstream pancreatic parenchyma and duct were found to terminate within the WON in all 21 patients in whom DPDS was subsequently confirmed by follow-up CT in all patients, by ERCP in 17, EUS-pancreatogram in 3 and surgical pathology in 1. There was 100 % correlation between EUS characterization of DPDS with CT and pancreatography or surgical pathology.Conclusions: We report EUS findings indicating the presence of DPDS. These findings may have significant clinical implications for the management of patients with WON.